Evaluation of a Dried Fermentation Product Administered Through Drinking Water in a Commercial Environment on Nursery Pig Mortalities, Antibiotic Injections, and Growth Performance - Alan J. Warner; Brittany Carrender; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt; Kyle F. Coble; Alain Labbé; Walter Heuser (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 34,399 commercial nursery pigs (initially 12.2 lb) were used in 20 nursery barns with 10 barns per treatment to determine the effectiveness of a dried fermentation product (DFP) on nursery pig mortalities, antibiotic injection frequency, and close-out growth performance. The target dosage of the DFP for the first 14 d was 35 mg/kg BW based on the actual dosage of a previous experiment. Following the 14-d supplementation period, pigs continued to be monitored until they were moved from the barn at approximately d 45. The first 6 replicates consisted of the DFP as the sole source of water additive from d 0 to 14, while the last 4 replicates included water-soluble antibiotics with the DFP. During the supplementation period, there was no evidence that the DFP influenced the percentage of pigs that died or total mortality. However, the DFP reduced the percentage of pigs that were euthanized. During the common period, the DFP increased the percentage of pigs euthanized and tended to increase mortality percentage. For the overall experiment, providing the DFP did not influence growth performance. When providing the DFP, there was an increase in the percentage of pigs requiring euthanasia and therefore an increase in overall mortality. For injections, providing the DFP for the first 14 d reduced the number of pigs injected from d 14 to d 45 by the end of the nursery and the overall nursery period.
Keywords: dried fermentation product; growth; nursery pig